Cdc13 Telomere Capping Decreases Mec1 Association but Does Not Affect Tel1 Association with DNA Ends - Hirano, Yukinori (The American Society for Cell Biology, 2007)
Chromosome ends, known as telomeres, have to be distinguished from DNA breaks that activate DNA damage checkpoint. Two large protein kinases, ataxia-teleangiectasia mutated (ATM) and ATM-Rad3-related (ATR), control not only checkpoint activation but also telomere length. In budding yeast, Mec1 and Tel1 correspond to ATR and ATM, respectively. Here, we show that Cdc13-dependent telomere capping attenuates Mec1 association with DNA ends. The telomeric TG repeat sequence inhibits DNA degradation and decreases Mec1 accumulation at the DNA end. The TG-mediated degradation block requires binding of multiple Cdc13 proteins. The Mre11–Rad50-Xrs2 complex and Exo1 contribute to DNA degradation at DNA ends. Although the TG sequence impedes Exo1 association with DNA ends, it allows Mre11 association. Moreover, the TG sequence does not affect Tel1 association with the DNA end. Our results suggest that the Cdc13 telomere cap coordinates Mec1 and Tel1 accumulation rather than simply covering the DNA ends at telomeres.